Improving the mechanism of collecting certain taxes in Ukraine as measures for the European modernization: legal aspect - Holovko, Oleksandr; Kaganovska, Tetyana; Rossіhіna, Galina (Riga : Publishing House “Baltija Publishing”, 2018)
The aim of the article is to study the methodological and theoretical principles of improving the legal regulation of the taxation system in Ukraine in the European integration context. Determination of the doctrinal basis for the implementation of the tax function of the state and its legal consolidation from the standpoint of the fundamental principles of the law allows carrying out a comparative legal analysis of taxation in the developed countries of Europe and the world (particularly indirect one). Methodology. The research is based on the theoretical and legal substantiation of the social content of tax activities in the state, and it is also based on the understanding of the dialectical relationship between tax processes and the functioning of social and legal systems in general. A systematic analysis of the tax activity of the state in the context of humanism, justice, freedom, equality, rule of law is carried out. On this basis, the legal nature of the regulation of the value-added tax is revealed. Results. The basic theoretical and legal bases of measures on improvement of the taxation system are determined as a result of the study from the position of its legitimation among citizens and stimulation of their purchasing power and development of productive forces of the Ukrainian economy. Practical impact. The definition of directions for perfection and humanization of tax legislation in Ukraine allows making a conclusion about the volume of the tax burden on the consumer and proposing optimal rates of value-added tax rates.
Keywords: LAW/JURISPRUDENCE; social nature and legal nature of taxation; equity of taxes; value added tax; tax pressure; optimization of tax rates